PENETAPAN KADAR FLAVONOID EKSTRAK KULIT BUAH NYIRIH (Xylocarpus granatum) BERDASARKAN VARIASI PELARUT DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Elgi Nurul Hidayah; Achmad Kadri Ansyori; Henny Nurhasnawati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
The plant Nyirih (Xylocarpus granatum) has medicinal benefits. The selection of solvents should consider the characteristics of the secondary metabolites to be extracted. The objective of this study is to determine the flavonoid content in Nyirih fruit extract using 70% methanol and 70% ethanol solvents using UV-Vis spectrophotometry. The results of the moisture content test showed 24% for methanol extract and 28.5% for 70% ethanol extract. Phytochemical screening of Nyirih fruit extract in methanol and 70% ethanol solvents tested positive for flavonoid content. Thin layer chromatography (TLC) results showed an rf value of 0.88 for both solvents, while the reference compound, quercetin, had an rf value of 0.90. The highest flavonoid content was found in the 70% ethanol extract at 1.4345 ± 0.2182% and in the methanol extract at 1.3530 ± 0.2280%. The t-test results indicated a significant difference in the flavonoid content value.